2000
DOI: 10.1039/b003739g
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonation of [Mo(COMe)(CO)2(PPh2H)(η-C5H5)] and reaction with activated alkynes: controllable formation of vinylphosphine and η3-acryloyl ligands

Abstract: Deprotonation of the secondary phosphine ligand in the complex [Mo(COMe)(CO) 2 (PPh 2 H)(η-C 5 H 5 )] 1 with DBU (1,8-diazabicyclo[5.4.0]undec-7-ene) at Ϫ78 ЊC followed by reaction with DMAD (dimethyl acetylenedicarboxylate, MeO 2 CC᎐ ᎐ ᎐ CCO 2 Me) afforded the vinylphosphine complex trans-[Mo(COMe)(CO) 2 {PPh 2 C(CO 2 Me)᎐ ᎐ CHCO 2 Me}-(η-C 5 H 5 )] 2a after protonation. The crystal structure of this compound confirms that the phosphine ligand is formed exclusively as the Z isomer. A similar reaction employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The 13 C{ 1 H} NMR spectrum for the absolute major isomer cis - 2A displays a highly deshielded acyl resonance at 276 ppm, a chemical shift similar to those in complexes of the type [MoCp{C(O)R}(CO) 2 (PR′ 3 )] . Moreover, the carbonyl ligands give rise to three distinct resonances, with chemical shifts and P−C couplings comparable to those of the isoelectronic cis -[Mo 2 Cp 2 (μ-COMe)(μ-PCy 2 )(CO) 3 ] and cis -[Mo 2 Cp 2 {μ-κ 1 :η 2 -HCCRH}(μ-PCy 2 )(CO) 3 ] …”
Section: Resultsmentioning
confidence: 91%
“…The 13 C{ 1 H} NMR spectrum for the absolute major isomer cis - 2A displays a highly deshielded acyl resonance at 276 ppm, a chemical shift similar to those in complexes of the type [MoCp{C(O)R}(CO) 2 (PR′ 3 )] . Moreover, the carbonyl ligands give rise to three distinct resonances, with chemical shifts and P−C couplings comparable to those of the isoelectronic cis -[Mo 2 Cp 2 (μ-COMe)(μ-PCy 2 )(CO) 3 ] and cis -[Mo 2 Cp 2 {μ-κ 1 :η 2 -HCCRH}(μ-PCy 2 )(CO) 3 ] …”
Section: Resultsmentioning
confidence: 91%
“…The acyl groups in compounds 2 a,b give rise to highly deshielded 13 C NMR resonances in the range d = 263-271 ppm, a position comparable to those of mononuclear molybdenum complexes with acyl ligands. [18] A mediumintensity IR band in the range 1500-1600 cm À1 was also observed in these compounds, which can be assigned to the corresponding C À O stretch. For compounds 3 a,b, the iminoacyl group gives rise to a less deshielded resonance at around d = 206 ppm, which is close to the values of d = 220 ppm recently reported for the related phosphametallacycles in the niobium complexes [Nb(C 5 H 4 SiMe 3 ) 2 {k 1 ,h 1 -Ph 2 PCR = CR'C(NXyl)].…”
mentioning
confidence: 84%
“…When we treated [CpMo (CO) 3 ] À with DMAD in a similar manner, an immediate reaction of the two compounds occurred, but on addition of H + , the only isolated product was [Cp 2 Mo 2 (CO) 6 ]. It appears that the r-vinyl complexes of tungsten may be rather more stable than those of molybdenum.…”
Section: Reaction With Activated Alkynesmentioning
confidence: 96%
“…We have previously reported that the anion [CpMo(CO) 2 (PPh 2 COMe)] À , prepared by deprotonation of [CpMo(CO) 2 (PPh 2 H)(COMe)] at room temperature (which induces a migration of the acyl group from molybdenum to phosphorus) reacts with RC"CCO 2 Me (R = H, CO 2 Me) to give the acryloyl complexes [CpMo(CO)(PPh 2-COMe)(g 3 -COCR@CHCO 2 Me)] together with much lower yields of associated vinyl complexes [6]. We therefore sought to establish whether this was a general reaction of substituted carbonyl anions of the type [CpMo(CO) 2 (L)] À with tertiary phosphine ligands, and in this paper we report our results which show that this is indeed the case.…”
Section: Introductionmentioning
confidence: 99%